The angiotensin II/type 1 angiotensin II receptor pathway is implicated in the dysfunction of albumin endocytosis in renal proximal tubule epithelial cells induced by high glucose levels - Afonso, Liz G.; Silva-Aguiar, Rodrigo P.; Teixeira, Douglas E.; Alves, Sarah A.S.; Schmaier, Alvin H.; Pinheiro, Ana Acacia S.; Peruchetti, Diogo B.; Caruso-Neves, Celso (Biochimica et biophysica acta. General subjects, 2024)
It is well-established that dysfunction of megalin-mediated albumin endocytosis by proximal tubule epithelial cells (PTECs) and the activation of the Renin-Angiotensin System (RAS) play significant roles in the development of Diabetic Kidney Disease (DKD). However, the precise correlation between these factors still requires further investigation. In this study, we aimed to elucidate the potential role of angiotensin II (Ang II), a known effector of RAS, as the mediator of albumin endocytosis dysfunction induced by high glucose (HG) in PTECs. To achieve this, we utilized LLC-PK1 and HK-2 cells, which are well-established in vitro models of PTECs. Using albumin-FITC or DQ-albumin as tracers, we observed that incubation of LLC-PK1 and HK-2 cells with HG (25 mM for 48 h) significantly reduced canonical receptor-mediated albumin endocytosis, primarily due to the decrease in megalin expression. HG increased the concentration of Ang II in the LLC-PK1 cell supernatant, a phenomenon associated with an increase in angiotensin-converting enzyme (ACE) expression and a decrease in prolyl carboxypeptidase (PRCP) expression. ACE type 2 (ACE2) expression remained unchanged. To investigate the potential impact of Ang II on HG effects, the cells were co-incubated with angiotensin receptor inhibitors. Only co-incubation with 10−7 M losartan (an antagonist for type 1 angiotensin receptor, AT1R) attenuated the inhibitory effect of HG on albumin endocytosis, as well as megalin expression. Our findings contribute to understanding the genesis of tubular albuminuria observed in the early stages of DKD, which involves the activation of the Ang II/AT1R axis by HG. •HG inhibits the canonical receptor-mediated albumin endocytosis in PTECs.•Ang II concentrations at LLC-PK1 cell supernatant are increased by HG.•HG upregulates ACE expression while downregulating PRCP expression in PTECs.•The Ang II / AT1R pathway mediates the inhibitory effect of HG on albumin endocytosis.•Changes in megalin expression correlate with the inhibition of albumin endocytosis induced by HG.